Tailored products of dealloying as-sintered Al–Cu alloys in sodium hydroxide solutions1. Issue 92 (8th October 2015) - Li, Jie; Yang, Zhongxi; Wang, Tianning; Yu, Nana; Sun, Lanju; Nie, Chen; Teng, Huaide; Jin, Cheng; Chen, Xiutong; Geng, Haoran
<x xml:space="preserve">Abstract</x> In this work, a two-step method of cold-press sintering–dealloying was applied to fabricate nanostructured copper/copper oxides mixtures.